Meningkatkan Kesadaran dan Partisipasi Masyarakat dalam Pengelolaan Sampah di Desa Sukajadi - Ausaf, Dafa (Jurnal Pengabdian Tri Bhakti, 2025)
This community service program was motivated by the issue of low awareness and inadequate facilities for waste management in Sukajadi Village, Bandung Regency. The main objective is to improve environmental literacy among residents and encourage behavioral change toward sustainable household waste management. The methods used include the Participatory Rural Appraisal (PRA) to identify problems through community participation and Community Development (CD) to empower local communities. The program involved educational seminars, installation of waste education signage, ecoproduction training (such as crafting from waste and organic pesticide production), and the development of the Sukajadi Village Digital Waste Bank Website as a digital solution. The results showed increased ecological awareness, especially among the younger generation, active participation in environmental activities, and the emergence of positive waste management habits. The digital waste bank platform became a strategic innovation for easy monitoring and ongoing education. The implication of this program is the establishment of a foundational environmental care culture that has the potential to evolve into a sustainable, locally-based social movement.